KONTRIBUSI DAN DAYA SAING EKSPOR SEKTOR UNGGULAN DALAM PEREKONOMIAN JAWA TENGAH - Achmad Soleh; Darwanto Darwanto (Universitas Diponegoro, 2012)
ABSTRACT Leading sectors in Central Java provides a large multiplier effect on regional economies, but in the development of this sector requires the ability to grow and become the locomotive of growth for other sectors. High market a boost, especially in export demand will encourage sectors to be able to grow taller and encourages other sectors to grow. This study aims to analyze the contribution and the competitiveness of export sectors in Central Java. Input-output analysis is used to look at linkages between sectors that may ultimately be determined to be the key sector. Based on the key sector contribution can be seen later multiplier can also be shown from these sectors. Analysis of RCA (Revealed comparative advantage) is used to look at the competitiveness of export sectors. Estimation of linkage in this study using input-output tables of Central Java in 2008 with a classification of 88 sectors are aggregated into 87 sectors. The analysis based on linkages between sectors of economic sectors in Central Java shows there are 16 sectors in Central Java. Of the 16 sectors in the economy of Central Java are in almost all sectors of manufacturing industry sectors. This indicated that Central Java was instrumental in the development of processing industry in Indonesia. The results of the analysis of contribution (share) note that the sectors that contributed most to the total output is the sector of oil and fat industry, wood industry and building materials of wood, and electricity and gas sectors. Based on the analysis of export competitiveness (Revealed Comparative Advantage) shows the dominant sector in Central Java with the export competitiveness of the timber and building materials of wood, non-metallic mineral products industry, spinning mill industry, cement industry, and the lime industry. RCA values ​​indicates that the leading sectors have export competitiveness.